The impact of wisdom and courage on presencing and absencing at work - Balas Rant, Melita (Economic and business review, 2023)
Background and Objective: Wisdom and courage are positive psychological capacities. Presencing and absencing at work are novel employee attitudes and behaviours. The objective of this paper is to explore the impact of wisdom and courage on presencing and absencing at work, while also considering possible mediation through mindfulness. Methods: This paper hypothesises that wisdom has a positive impact on presencing and a negative impact on absencing, while courage has a negative impact on presencing and a positive impact on absencing. We expect mindfulness mediates the aforementioned relationships. An analysis is performed on a sample of 274 employees in Slovenia by applying structural equation modelling. Results: The test results have shown that wisdom has a negative impact on absencing at work, while courage has a positive impact on absencing at work. These impacts are mediated through mindfulness. The major weakness of this research design is a low sample size and the weak construct reliability of wisdom and courage. Conclusions: Wisdom and courage have opposing effects on presencing and absencing at work. Mindfulness is an important mediator. Contribution/value: This research contributes to positive organisational behaviour by showing that positive psychological capacities (i.e., wisdom, courage, mindfulness) are important predictors of employee presencing and absencing.
Keywords: absenteeism; kadri; odsotnost z dela; organizacija; organization; personnel